2023
DOI: 10.1021/acs.est.3c00086
|View full text |Cite
|
Sign up to set email alerts
|

Transport Pathways of Nitrate Formed from Nocturnal N2O5 Hydrolysis Aloft to the Ground Level in Winter North China Plain

Abstract: Particulate nitrate (NO3 –) has currently become the major component of fine particles in the North China Plain (NCP) during winter haze episodes. However, the contributions of formation pathways to ground NO3 – in the NCP are not fully understood. Herein, the NO3 – formation pathways were comprehensively investigated based on model simulations combined with two-month field measurements at a rural site in the winter NCP. The results indicated that the nocturnal chemistry of N2O5 hydrolysis aloft could contribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…The importance of the NO 3 + HC pathway in nitrate production has been a subject of debate among different research approaches. However, both chemical transport models and observation‐based box models have shown that this pathway does not contribute significantly to nitrate production in winter Beijing haze (Chan et al., 2021; X Chen et al., 2020; H Wang, Lu, Guo, et al., 2018; Xie et al., 2022; Zhao et al., 2023; H Wang et al., 2021). For instance, an analysis of the long‐term NO 3 radical budget in the winter of 2014–2019 in Beijing demonstrated that N 2 O 5 heterogeneous hydrolysis was the dominant process responsible for total NO 3 radical loss, accounting for 77%–92% (H Wang et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The importance of the NO 3 + HC pathway in nitrate production has been a subject of debate among different research approaches. However, both chemical transport models and observation‐based box models have shown that this pathway does not contribute significantly to nitrate production in winter Beijing haze (Chan et al., 2021; X Chen et al., 2020; H Wang, Lu, Guo, et al., 2018; Xie et al., 2022; Zhao et al., 2023; H Wang et al., 2021). For instance, an analysis of the long‐term NO 3 radical budget in the winter of 2014–2019 in Beijing demonstrated that N 2 O 5 heterogeneous hydrolysis was the dominant process responsible for total NO 3 radical loss, accounting for 77%–92% (H Wang et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…1 In recent years, excess nitrate (NO 3 − ), caused by animal manure, nitrogen fertilizers and fossil fuels, has become a nitrogenous pollutant widely found in wastewater. 2,3 According to the World Health Organization (WHO) recommendations, the concentration of NO 3 − (or NO 3 − –N) in drinking water should be below 50 mg L −1 (or 11.3 mg L −1 ), otherwise it may cause a serious health risk to aquatic plants and humans. 4–6 Nowadays, there are two major objectives for nitrate conversion, which are reducing the nitrates to ammonia (NH 4 + ) or nitrogen (N 2 ).…”
Section: Introductionmentioning
confidence: 99%